Effect of taxifolin and epigallocatechin-3-gallate on biomineralization potential of stem cells from dental apical papilla - Duque, Cristiane [UNESP] (2022)
Objective: Considering the variety of pharmacological activities and the potential to mediate biomineralization, the flavonoids taxifolin and epigallocatechin-3-gallate (EGCG) could be explored as biomolecules in scaffolds for regenerative endodontic procedures. The aim of this study was to evaluate the effect of taxifolin and EGCG on the cell viability, differentiation, and expression of biomineralization markers in stem cells from the apical papilla. Design: Stem cells from the apical papilla were exposed to single or continuous treatments with taxifolin at 200, 100 and 50 µM and EGCG at 50, 25 and 12.5 µM for 48 h, 8 and 14 days, in regular or mineralizing media. Cell viability, alkaline phosphatase activity and calcium deposition were analyzed using resazurin, p-nitrophenylphosphate and alizarin-based assays. Results: None of the flavonoid groups affected cell viability at 48 h, however at 8 and 14 days, Taxifolin 200 µM and EGCG 50 µM were cytotoxic. Cells did not express alkaline phosphatase activity when grown in regular medium, even in the presence of flavonoids. Alkaline phosphatase activity and biomineralization potential were higher in cells treated with Taxifolin 50 µM and EGCG 12.5 µM. Conclusion: Taxifolin and EGCG exhibited a concentration, time, and therapeutic mode dependent bioactivity on stem cells from the apical papilla. Both flavonoids at the lower concentrations tested exhibited cytocompatibility and increased expression of mineralization markers in the presence of mineralizing agents.